Performance of a solar-hydrogen stand-alone system for residential applications - Pinto, P. Ribeiro (2012)
Hydrogen, as an energy storage medium, is considered a promising solution to overcome the limitation of intermittent renewable energy sources. In this paper, a residential scale solar-hydrogen based stand-alone energy system is designed, modelled and the simulated system performance under real end-use load, representative of standard European domestic electrical energy consumption, and meteorological conditions is analyzed. The sun is the primary energy source of the system and a fuel cell-electrolyzer combination is used as a backup and a long-term storage system. A battery bank is also used as energy buffer and for short time storage. Matlab/Simulink® is used for the overall system modelling and simulation. The results show that the designed solar-hydrogen system is in principle capable of operating autonomously and in a sustainable manner. The designed system is able to convert 7.6% of the total energy irradiated in one year.